Pengaruh Diversifikasi Produk, Kompetensi Wirausaha Dan Desain Kemasan Terhadap Keberhasilan Usaha UMKM Minuman Herbal Di Kabupaten Bekasi - Eka Lestari; Junedi Junedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research originated from a concern for the challenges faced by herbal drink entrepreneurs in Bekasi Regency, Indonesia. As a country rich in spices, Indonesia has significant potential to develop its agricultural sector, including the production of herbal beverages. To address these challenges, product diversification becomes a key strategy to increase sales and develop effective marketing strategies by leveraging the entrepreneurs' competencies and attractive packaging designs. This study aims to describe the influence of product diversification, entrepreneurial competencies, and packaging design on the success of herbal drink businesses in Bekasi Regency. A quantitative research approach was employed. The results indicate that product diversification, entrepreneurial competencies, and packaging design have a positive and significant impact on business success.